"Türkçe Konuşan Rus Çarı" nın Kafkasya Seyahati (1837) ve Osmanlı Devleti - (:unkn) unknown (My University, 2004)
0

The interest of Russian Empire in the Caucasia riched the highest point with the trip of the Tsar Petro the first to the Caspian coast with excuse helping to Iran in the year 1722 while the Afghanistan and Iran were in strong dispite. After the Tsar Petro I. an other Russian tsar, Nicolai the first went on the trip to Caucasia in the year 1837. In this article it was dealt with the reflections of the trip of the Tsar Nicolai the first to Caucasia on the Ottoman Empire. Within the report which was written and than presented to the Capitol Istanbul by Esat Pasha who was sent to the city Gümrü to say "wellcome" to the Tsar in the name of the Ottoman Empire was generally evaluated. And in addition to whom it may concern, the whole transcription of the report is attached and thus it is struggeled to draw an attention to the importance of the issue.
The Trip of Turkish Speaking Russian Tsar Nicolai the First to Caucasia (1837) and the Ottoman Empire
Keywords: Tarih